2002
DOI: 10.1046/j.1365-2958.2002.02865.x
|View full text |Cite
|
Sign up to set email alerts
|

The transcription termination factor Rho is required for oxidative stress survival in Caulobacter crescentus

Abstract: Summary A transposon Tn5 mutagenesis library was generated from Caulobacter crescentus strain NA1000, and clones with deficiency in survival in a high concentration of NaCl were selected. One of these clones, 37G10, has the Tn5 integrated within the coding region of the transcription termination factor Rho. Analysis of this mutant phenotype showed that the cells are motile and present a normal cell cycle, but have a longer generation time. This strain is sensitive to acidic pH, to the presence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 46 publications
1
25
1
3
Order By: Relevance
“…Changes in the cellular redox state during co-culture may have been part of the signal sensed by the cell to elicit these responses, either directly transcription factors as described above, or through post-transcriptional regulation. Indeed, the abundance of Rho transcripts, a gene that has an important role in regulating transcriptional termination and contributes to oxidative stress survival in other bacteria (Italiani et al, 2002;Kawamura et al, 2005) decreased after 24 h of co-culture.…”
Section: Regulation Of Transcriptional Responses To Co-culturementioning
confidence: 99%
“…Changes in the cellular redox state during co-culture may have been part of the signal sensed by the cell to elicit these responses, either directly transcription factors as described above, or through post-transcriptional regulation. Indeed, the abundance of Rho transcripts, a gene that has an important role in regulating transcriptional termination and contributes to oxidative stress survival in other bacteria (Italiani et al, 2002;Kawamura et al, 2005) decreased after 24 h of co-culture.…”
Section: Regulation Of Transcriptional Responses To Co-culturementioning
confidence: 99%
“…However, the relative importance of Rhodependent termination varies between bacteria. In the proteobacteria E. coli and Rhodobacter sphaeroides, as well as the actinobacterium Micrococcus luteus, Rho is essential [10][11][12]; in the proteobacterium Caulobacter crescentus, Rho is required for oxidative stress survival [13]. Also, an analysis of the average RNA folding energy near stop codons suggested that no stem-loops are formed in the Firmicutes Mycoplasma genitalium and M. pneumoniae, the actinobacterium Mycobacterium pneumoniae, the cyanobacterium Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were tested for oxidative, saline, acidic, heat and UV exposure (Fig. 2), at conditions in which the wild type cells were not affected (12). As a second control, a mutant strain with the Tn5 inserted into the rsaF gene that encodes an outer membrane protein (OMP58) was tested for all stresses and responded like the wild type, indicating that the sensitivity to stress is not due to the presence of the Tn5 (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Tn5 (Kan) transposon was inserted into C. crescentus strain NA1000 by conjugation with an E. coli S17-1 carrying plasmid pSUP2021 (25) as described (12). Screeening was performed as described previously (28), with the following modifications: the cells were grown in 96-well plates containing 0.3 ml of PYE/Kan medium at 30ºC for 14 days with agitation, followed by plating in PYE/Kan.…”
Section: Isolation Of Stationary Phase Deficient Mutants From a C Crmentioning
confidence: 99%
See 1 more Smart Citation